(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Co-teaching or team teaching is the division of labor between educators to plan, organize, instruct and make assessments on the same group of students, generally in the a common classroom, and often with a strong focus on those teaching as a team complementing one another’s particular skills or other strengths.